Exploration of Halfmoon Betta Fish Tail Shapes Using Fan Pleats in an Evening Gown - Novia Syifana Nurchaliza; Mila Karmila (Universitas Negeri Semarang, 2025)
The beauty of nature, especially fauna, has become a source of inspiration in creating fashion designs. This exploration shows that elements from nature can be translated into innovative designs with high artistic value. This research explores the tail shape of the Halfmoon betta fish, which is known for its beauty and uniqueness, as inspiration in creating an evening gown using the fan-pleated technique. The purpose of this study is to create a new evening gown design that presents an elegant and unique character by applying the shape of the Halfmoon betta fish tail as the main design idea. The research method used is PPE (Planning, Production, and Evaluation). The planning stage involves exploring the shape and characteristics of the Halfmoon betta fish tail through the development of moodboard, mind maps, and detailed design sketches focusing on shape and color. The production stage applies the fan-pleated technique to the evening gown, while the evaluation stage involves feedback and suggestions from fashion experts regarding the final work. The results show that the application of the fan-pleated technique can aesthetically represent the shape of the betta fish tail and provide the gown with an elegant and unique appearance. In conclusion, exploring animal forms through fabric manipulation using the fan-pleated technique can be a source of innovation center of interest in evening gown design, highlighting the beauty of fauna in fashion.